The Identity Crisis of Islamic Boarding School Students in the Flow of Socio-Cultural Change - Amalia, Ilmi; Rahmi, Jumailatul; Geubrina, Manda (Institut Agama Islam Negeri Kediri, 2025)
Research The santri identity crisis is a phenomenon that arises due to the conflict between traditional pesantren values and modern social dynamics. Many santri experience confusion in determining their identity, especially when they have to balance between the religious values taught in pesantren and modern social demands such as the influence of social media and the expectations of the outside community. This phenomenon triggers anxiety, stress, and decreased motivation to learn. The research aims to identify the main causes of santri identity crisis, analyze how santri adapt to identity conflicts, and identify strategies that can help santri overcome identity confusion. The research used a qualitative method with a phenomenological approach with semi-structured interviews and participatory observation of santri and dayah administrators. The results showed that many santri are in the moratorium phase, where they experience identity exploration without a strong commitment to one particular identity. External factors such as social pressure, family expectations, and the influence of social media exacerbate santri's identity confusion, forcing them to balance between religious values and modern social norms. To deal with this, Dayah Malikussaleh implements adaptive policies through self-development programs, majlis ta'lim, and psychological guidance. This strategy helps santri navigate the moratorium phase, encouraging a balance between religious education and adaptive skills. This research highlights the importance of a holistic approach in pesantren education to support santri in achieving identity stability amidst dynamic social change.